Petroleum – Strategic Resource for World Economy (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
Petroleum is the most important resource for global energy production, far exceeding the role of coal and natural gas, the role of river energy and wind energy, and also the role of nuclear fuel. All highly industrialized countries are making great efforts to ensure the energy needs of the functioning of economies under the conditions of fierce global competition. None of the world's first 10-12 economies can give up on petroleum imports, and the exporting countries benefit from large financial resources from petroleum. Saudi Arabia, Qatar, United Arab Emirates, Venezuela, Russia and other petroleum-rich countries secure themselves significant foreign revenue for their economic development, defense and overall well-being.